Frequency-energy and amplification characteristics of the CuCl laser with an internal reactor - Shiyanov D. V. Dmitry Valeryevich; Trigub M. V. Maksim Viktorovich; Sukhanov V. B. Viktor Borisovich; Evtushenko G. S. Gennady Sergeevich; Vlasov V. V. (Optics, 2015)
Title screen